2013
DOI: 10.4236/ars.2013.21003
|View full text |Cite
|
Sign up to set email alerts
|

Remote Monitoring of Wheat Streak Mosaic Progression Using Sub-Pixel Classification of Landsat 5 TM Imagery for Site Specific Disease Management in Winter Wheat

Abstract: Wheat streak mosaic (WSM), caused by Wheat streak mosaic virus is a viral disease that affects wheat (Triticum aestivum L.), other grains, and numerous grasses over large geographical areas around the world. To improve disease management and crop production, it is essential to have adequate methods for monitoring disease epidemics at various scales and multiple times. Remote sensing has become an essential tool for monitoring and quantifying crop stress due to biotic and abiotic factors. The objective of our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 74 publications
(110 reference statements)
0
11
0
1
Order By: Relevance
“…They indicated that spectral reflectance contrasts and canopy characteristics between harm from disease contamination and harm from insect infestation can be measured by remote sensing in crop canopies. Mirik et al . ( 2013) (Mirik et al 2013) concluded that explicit Wheat Streak Mosaic Ailment infection at the site can be reliably classify and quantify by using the land sat 5 TM image.…”
Section: Abiotic and Biotic Factorsmentioning
confidence: 99%
“…They indicated that spectral reflectance contrasts and canopy characteristics between harm from disease contamination and harm from insect infestation can be measured by remote sensing in crop canopies. Mirik et al . ( 2013) (Mirik et al 2013) concluded that explicit Wheat Streak Mosaic Ailment infection at the site can be reliably classify and quantify by using the land sat 5 TM image.…”
Section: Abiotic and Biotic Factorsmentioning
confidence: 99%
“…Imagery was acquired biweekly, beginning in early March, and diseased wheat was separated from healthy wheat using a subpixel classifier with 491% accuracy (Mirik et al, 2013). A study was conducted to evaluate Landsat 5 TM imagery for detection, quantification, and mapping of WSM in irrigated wheat fields.…”
Section: Development Of An Economic Threshold For Site-specific Variamentioning
confidence: 99%
“…Based on the acceptable spatial and temporal resolutions, multispectral satellite technique becomes a feasible method for crop diseases and pests monitoring [8,14,15]. For instance, based on Landsat-5 Thematic Mapper (TM) data, Mirik et al [16] successfully assessed the infection and progression of wheat streak mosaic. Navrozidis et al [17] demonstrated that field spectroscopy and wide area remote sensing (i.e., Landsat-8) can be used to create sufficiently accurate quantification models of crop disease severity.…”
Section: Introductionmentioning
confidence: 99%